2020
DOI: 10.2337/db20-0207
|View full text |Cite
|
Sign up to set email alerts
|

VMAT2 Safeguards β-Cells Against Dopamine Cytotoxicity Under High-Fat Diet–Induced Stress

Abstract: Vesicular monoamine transporter 2 (VMAT2) uptakes cytoplasmic monoamines into vesicles for storage. VMAT2 plays a role in modulating insulin release by regulating dopamine levels in the pancreas, although the exact mechanism remains elusive. We found that VMAT2 expression in β-cells specifically increases under high blood glucose conditions. The islets isolated from β-cell–specific Vmat2 knockout (βVmat2KO) mice show elevated insulin secretion levels in response to glucose stimulation. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Recently, Daisuke et.al. reported that ROS production directly triggers the dedifferentiation of β-cells in the islets of β-cell-specific vesicular monoamine transporter 2 knock-out mice [ 66 ]. However, it is unclear whether ROS induces β-cell dedifferentiation without an intermediate role of inflammatory cytokines.…”
Section: Potential Mechanisms Regulating β-Cell Dedifferentiationmentioning
confidence: 99%
“…Recently, Daisuke et.al. reported that ROS production directly triggers the dedifferentiation of β-cells in the islets of β-cell-specific vesicular monoamine transporter 2 knock-out mice [ 66 ]. However, it is unclear whether ROS induces β-cell dedifferentiation without an intermediate role of inflammatory cytokines.…”
Section: Potential Mechanisms Regulating β-Cell Dedifferentiationmentioning
confidence: 99%
“…Thus, PLUTO may suppress the dedifferentiation of pancreatic β-cells [ 45 , 46 ]. In pancreatic β-cell-specific vesicular monoamine transporter 2 (VMAT2) knockout mice, mature β-cell markers (Ins1, Ins2, MafA, Nkx6.1, Gck, and Pdx-1) decreased with age, and the expression of MafB, an immature β-cell or a mature α cell marker, was upregulated [ 47 ]. GLP-1 is also involved in the suppression of pancreatic β-cell dedifferentiation.…”
Section: Pancreatic β-Cell Dedifferentiation and Transdifferentiationmentioning
confidence: 99%
“…ROS causes reduction of MafA and Pdx-1 expressions, transcription factors required for the development and maintenance of pancreatic β-cells, thereby promoting the dedifferentiation of pancreatic β-cells and decreasing insulin secretion [ 13 , 14 ]. In recent years, antioxidant administration has been reported to protect pancreatic β-cells in obese type 2 diabetes model mice and pancreatic β-cell lines (HIT-T15) [ 14 , 15 ] and VMAT2, which is expressed in pancreatic β-cells, has been shown to suppress oxidative stress through modulation of dopamine levels in pancreatic β-cells, resulting in inhibition of pancreatic β-cell death and dedifferentiation [ 47 ]. In addition, FoxO1 has also gained attention as an inhibitor of pancreatic β-cell dedifferentiation.…”
Section: Pancreatic β-Cell Dedifferentiation and Transdifferentiationmentioning
confidence: 99%
“…Finally, VMAT2 is expressed in insulin-secreting beta cells of the pancreas and may safeguard them against dopamine toxicity during stress induced by a high-fat diet. 9 To investigate the consequence of abnormal VMAT2 on embryonic development and adult physiology several lines of Vmat2 mutant mice have been generated. [10][11][12][13] Mice homozygous for loss-of-function alleles of Vmat2 do not grow into adulthood.…”
Section: Introductionmentioning
confidence: 99%